2017
DOI: 10.1055/s-0037-1606114
|View full text |Cite
|
Sign up to set email alerts
|

Intersphincteric Resection Pushing the Envelope for Sphincter Preservation

Abstract: During the last 15 years, a significant evolution has emerged in the surgical treatment of rectal cancer and restoration of bowel continuity has been one of the main goals. For many years the treatment of distal rectal cancer would necessarily require an abdominoperineal resection and end colostomy. The surgical procedure of intersphincteric resection has been proposed to offer sphincter preservation in patients with low rectal cancer and has been legitimized if executed according to adequate oncologic criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…In daily practice, we avoid ISR only in patients with reported incontinence episodes. Denost et al reported that with a step-up strategy face to a bad anal function with low fiber diet, bulking agents, glycerol-based enemas, loperamide, sphincter re-education by biofeedback, sacral nerve stimulation, and cecostomy for anterograde enema, only 5% of the patients need a definitive stoma formation due to major and refractory fecal incontinence in their experience (73).…”
Section: Patient Selectionmentioning
confidence: 99%
“…In daily practice, we avoid ISR only in patients with reported incontinence episodes. Denost et al reported that with a step-up strategy face to a bad anal function with low fiber diet, bulking agents, glycerol-based enemas, loperamide, sphincter re-education by biofeedback, sacral nerve stimulation, and cecostomy for anterograde enema, only 5% of the patients need a definitive stoma formation due to major and refractory fecal incontinence in their experience (73).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Coupled with increasing knowledge regarding local and lymphatic spread, a level of resection with concomitant sphincter preservation can be achieved in patients with ultralow rectal cancer down to 2 cm from the dentate line. Ultralow and intersphincteric rectal resection with coloanal anastomosis together with neoadjuvant chemotherapy/radiotherapy have led to excellent oncological results, with avoidance of a permanent stoma.…”
Section: Introductionmentioning
confidence: 99%
“…It is pity that the number of lymph nodes harvested in the L-ISR of Baek's study was <12, which might cause the result inaccurate ( 14 ). Second, ISR surgery is more applicable for patients with T1 and T2 ( 30 ). Surgeons usually performed shorter resections with minimal lymph node dissection for this kind of tumors ( 31 ).…”
Section: Discussionmentioning
confidence: 99%